The last supper the plight of Christians in Arab lands - Wivel, Klaus 1971-; Kline, Mark (New York New Vessel Press, 2016)
"Alarmed by scant attention paid to the hardships endured by the 7.5 million Christians in the Middle East, journalist Klaus Wivel traveled to Iraq, Lebanon, Egypt, and the Palestinian. He found an oppressed minority under threat of death and humiliation and increasingly desperate in the face of rising Islamic extremism. Wivel spoke with priests whose churches have been burned, citizens who feel like strangers in their own countries, and entire communities whose only hope for survival may be fleeing into exile. This is an unsettling account of a severely beleaguered religious group living, so it seems, on borrowed time. Wivel asks, why have we not done more to protect these people?"--Page [4] of cover
Translated from the Danish
Includes bibliographical references and index
Text in English
Keywords: Christians -- Middle East -- History -- 21st century; Church History -- 21st century; Arab countries -- Religion -- 21st century